A collaborative multimodal working environment for the development of instrumental and professional competences of student translators: an innovative teaching experience. Issue 1 (2nd January 2016) - Prieto-Velasco, Juan Antonio; Fuentes-Luque, Adrián
ABSTRACT: Situated learning is based on the premise that action is grounded in the concrete situation and the specific circumstances in which it occurs. Such situatedness involves translation students working with authentic projects and developing professional skills, as translation needs to be undertaken within a particular framework where translators interact with colleagues and use tools for problem-solving tasks. In profession-oriented approaches to translator education, situated learning encourages the construction of new knowledge upon real-life working environments, which have evolved towards multimodal collaborative work scenarios which, in turn, simulate real-life workplaces. In order to help trainee translators develop instrumental and professional competences, we present an experimental study aimed at measuring students' academic performance in a project-based role play translation task. The study involves students using Web 2.0 tools for the translation of authentic texts on the basis of a realistic translation commission. The results point to a highly positive attitude of students towards Web 2.0 tools. Students found them very useful, interaction among team members was facilitated, and learning performance showed a significant improvement, with students feeling more confident, autonomous and encouraged by facing a realistic situation.